1989
DOI: 10.1021/jf00086a060
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in growth and chemical constituents of tobacco in response to carbon dioxide enrichment

Abstract: likely would be accompanied by changes in the concentration of important secondary compounds within leaves and on the leaf surface, possibly due to dilution effects or altered metabolism.The available evidence thus suggests that future increases in atmospheric C02 could have a considerable impact on yield and quality of tobacco. This investigation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
(15 reference statements)
1
5
0
Order By: Relevance
“…These studies showed that decreased levels of primary metabolites (amino acids, sugars) in tobacco leaves lead to a dramatic decrease in levels of nitrogen-and carbon-rich secondary metabolites (nicotine, CGA). Decreased levels of alkaloids in plants cultivated at elevated CO 2 have also been reported from field experiments, but the nitrogen state of the plants was not controlled in these experiments (Rufty et al 1989). Our results clearly demonstrate the necessity to carefully interpret experiments at high CO 2 and the requirement of differentiation between several plant tissues as well as between various groups of phenylpropanoids and other classes of secondary metabolites.…”
Section: Elevated Co 2 Leads To Altered Profiles Of Secondary Metabolsupporting
confidence: 67%
“…These studies showed that decreased levels of primary metabolites (amino acids, sugars) in tobacco leaves lead to a dramatic decrease in levels of nitrogen-and carbon-rich secondary metabolites (nicotine, CGA). Decreased levels of alkaloids in plants cultivated at elevated CO 2 have also been reported from field experiments, but the nitrogen state of the plants was not controlled in these experiments (Rufty et al 1989). Our results clearly demonstrate the necessity to carefully interpret experiments at high CO 2 and the requirement of differentiation between several plant tissues as well as between various groups of phenylpropanoids and other classes of secondary metabolites.…”
Section: Elevated Co 2 Leads To Altered Profiles Of Secondary Metabolsupporting
confidence: 67%
“…In contrast to the numerous observations on effects of elevated CO 2 levels on total leaf nitrogen, quantitative effects of CO 2 on specific nitrogen-containing defensive plant compounds have rarely been reported (Rufty et al, 1989;Frehner et al, 1997;Gleadow et al, 1998Gleadow et al, , 2009Goverde et al, 1999;Bazin et al, 2002). However, differentiation of compounds contributing to the overall leaf nitrogen pool is important, because these compounds may have completely different functions in interactions with higher trophic levels (Mattson, 1980;Baldwin, 1994;Ballhorn et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As far as we are aware, there has been only one other study of the effect of elevated CO 2 on nitrogen‐based defence compounds. This study, which examined nicotine in tobacco (Rufty et al 1989), reported a decrease in nicotine as a proportion of leaf dry weight in cured, field‐grown tobacco leaves grown at twice‐ambient CO 2 . This result, while conflicting with our own, is consistent with the relatively constant relationship between nicotine and leaf nitrogen measured in well fertilized plants (Baldwin & Ohnmeiss 1994), assuming that leaf nitrogen declined under high CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not the increase in nitrogen‐use efficiency of plants grown at elevated CO 2 allows nitrogen in excess of photosynthetic requirements to be reallocated to other functions, such as constitutive nitrogen‐based defence compounds, has not been resolved. We are aware of only one study examining the effect of enhanced CO 2 on nitrogen‐based secondary metabolites; it demonstrated no increase in nicotine in cured leaves from field‐grown tobacco exposed to twice‐ambient CO 2 concentration (Rufty et al 1989). Bearing in mind that nicotine concentration is highly dependent on nitrogen supply (Baldwin & Ohnmeiss 1994), it is not possible to draw conclusions about the relative allocation of nitrogen to defence from the results of Rufty et al as they did not measure total leaf nitrogen.…”
Section: Introductionmentioning
confidence: 99%